"Assata Shakur Is Welcome Here": Havana, Black Freedom Struggle, and U.S.–Cuba Relations. Issue 4 (2nd October 2017) - Latner, Teishan A.
Abstract : This article examines the Cuban exile of Assata Shakur, a former Black Panther who was granted formal political asylum by the government of Fidel Castro in 1984. Cuba's provision of sanctuary to Shakur and other U.S. Black activists offers new insights into the complex relationship between the African American freedom struggle and the Cuban Revolution. This article examines the politics of Shakur's exile in Havana, her significance within the Black radical imagination, and the influence of her exile upon U.S.–Cuba relations amid the Cold War and the War on Terror. It argues that Shakur's exile demonstrates the wedding of Washington's longstanding antipathy toward the Cuban Revolution with its persistent attempts to destroy U.S. Black radical movements. Melded together now within the discourse of "anti-terrorism, " Washington's hostility toward both Cuba and the legacy of the Black Panther Party suggests the durability of these antagonisms long after the decline of the Black Power and Cold War eras to which they are normally linked.